The effect of joint configuration on residual stress and distortion of the 304 stainless steel multi-pass welded joints. (March 2022) - Zhang, Yuelin; Tian, Li
Abstract: With the increasing of the dimension of engineering structures, the application of multi-pass welding is increasing. In this paper, numerical simulation of a thick plate's multi-pass welding process is carried out based on thermal elastic-plastic FEM, MSC. Marc software is used. The influence of plate thickness and joint configuration on welding distortion and residual stress is investigated. The results show that once other parameters are fixed, the thicker the plate, the larger the welding residual stress. Double V-groove joint has apparent refraining effect on transverse residual stress, while its influence on longitudinal stress is slight. For the compressive stress of the structure's bottom surface, double V-groove joint is better; while for the tensile stress of the structure's top surface, V-groove joint is better. The distortions of cross-sections increase with the increase of the plate thickness. Using double V-groove joint cannot only refrain the angular deformation of the multi-pass welded plate effectively, but also refrain its longitudinal deformation.